Using research priority-setting to guide bridging the implementation gap in countries - a case study of the Uganda newborn research priorities in the SDG era - Peter Waiswa; Monica Okuga; Lydia Kabwijamu; Joseph Akuze; Hanifah Sengendo; Patrick Aliganyira; Patricia Pirio; Claudia Hanson; Frank Kaharuza (BMC, 2019)
Abstract Background One of the greatest challenges that countries face regarding the achievement of the Sustainable Development Goal (SDG) targets for child health regard the actions required to improve neonatal health; these interventions have to be informed by evidence. In view of the persisting high numbers of newborn deaths in Uganda, we aimed to define a locally contextualised national research agenda for newborn health to guide national investments towards SDG targets. Methods We adopted a systematic approach for priority-setting adapted from the Child Health and Nutrition Research Initiative. We identified and listed local newborn researchers and experts in Uganda by reviewing the PubMed database, through a snowballing technique, and engaged the Ministry of Health. Participants were requested to generate at least three research questions. The collated questions were sent to the same expert group to be rated using five criteria, including answerability, scalability, impact, generalisability and speed. Findings Of the 300 researchers and stakeholders contacted, 104 responded (36%) and generated 304 questions. These questions were collated and duplicates removed giving a condensed list of 41 research questions. These questions were then rated by 82 experts. Of the top 15 research questions, 86.7% (13/15) were in the service delivery and 6.7% (1/15) in the development domain, while only 6.7% (1/15) was in the group 'other'. None of the leading 15 questions was in the discovery domain. Strategies to improve quality of intrapartum care featured high in the responses, while research around care for premature babies was not a perceived focus of research. Conclusions The focus of improved evidence to guide and innovate service delivery, foremost intrapartum care, reflects the importance of this area as accelerated improvement is likely to yield fast and sustained survival gains in the neonatal period and beyond in Uganda. We recommend that other countries adapt a similar approach in defining priority reproductive, maternal, newborn and child health areas for investment in order to accelerate progress towards achieving the SDGs.